Seeds of change eaudiobook Five plants that transformed mankind. - Hobhouse, Henry (Recorded Books Inc., 1987)
How did quinine, tea, cotton, sugar, and the potato change the face of world history? Five fascinating tales in which the unwitting heroes are plants and spices.